Узагальнені розв'язки для лінійних операторів з послабленими апріорними нерівностями - Анікушин, А.В.; Номіровський, Д.А. (Український математичний журнал, 2010)
Предлагается подход к изучеиию обобщенных решений линейных операторов, удовлетворяющих ослабленным априорным неравенствам. Этот подход обобщает ряд известных определений обобщенных решений операторных уравнений. Доказаны теоремы существования и единственности обобщенного решения. We propose an approach to the investigation of generalized solutions of linear operators that satisfy weakened a priori inequalities. This approach generalizes several well-known definitions of generalized solutions of operator equations. We prove existence and uniqueness theorems for a generalized solution.